An Investigation of Compliance with International Financial Reporting Standards by Listed Companies in Turkey - Volkan Demir; Oguzhan Bahadir (Journal of Accounting and Management Information Systems (JAMIS), 2014)
This study investigates the extent of compliance with international financial reporting standards (IFRSs) by listed companies in Turkey. Based on a sample of 168 companies we investigate the extent to which companies comply with IFRS disclosure requirements in their year - 2011 financial statements. Compliance levels range from 64 percent to 92 percent, with an average of 79 percent. The results unveil a considerable extent of non-compliance. The overall level of compliance with IFRSs disclosures is positively related to firms being audited by Big 4 auditing firms. Compliance is also negatively associated with the level of leverage. Other company characteristics, such as profitability, company size and age are determined to be statistically insignificant in explaining the level of disclosure compliance with IFRSs. The findings add to the growing concerns regarding the lack of effective monitoring in the Turkish capital market.
Keywords: M41; 650; IFRS implementation; IFRS compliance; disclosure checklist; company characteristics; Turkey